IMF Survey, Volume 31, Issue 15. (IMF Survey; IMF Survey ;, 2002)
On July 17, IMF First Deputy Managing Director Anne Krueger addressed a National Bureau for Economic Research (NBER) conference on the lessons to be learned from the Argentina crisis and how these can be used to raise the effectiveness of IMF efforts to prevent and resolve financial crises. Following are edited excerpts from her remarks; the full text is available on the IMF's website (www.imf.org).